Learning from Problem-Based Projects in Cross-Disciplinary Student Teams - Pål Ellingsen; Trude Tonholm; Frode Ramstad Johansen; Gunnar Andersson (MDPI AG, 2021)
This paper explores how Engineering students and Work and Welfare students reflect upon their own engagement in a one-week cross-disciplinary project. To develop a better understanding of what unfolds during these activities we collected data through anonymous surveys two consecutive years. Data from these 141 respondents were analysed using a learning history approach and are presented as narratives. Results show major disruptions and conflicts driving the student projects, exposing inviting confrontations, social identity threats, managing diversity, and friction of ideas. Whereas this in many cases led to new and better project solutions, these real-world experiences raise awareness of the need for tools and methods for training students. The aim of the paper is to learn from students' experiences through narrative distance, and fill a gap in the literature between problem-based learning (PBL) and the learning history method. Discussing different experiences of cross-disciplinary teamwork through the explanations of these theories, we also lay out potential questions for future research on the topic.